Exploration of longitudinal data based on integrated elderly health care for developing predictive health status in Semarang, Indonesia - Rosha, Putri Tiara; Oksidriyani, Safrina; Siyam, Nur; Meisyaroh, Indriani; Amalia, Laila; Fakhira, Azradina; Indah Setyowati, Florensia; Prastika, Yuniar Dwi (Universitas Gadjah Mada, 2024)
Purpose: This study aims to explore and describe vital sign measurements in the 20 periods. Methods: This study used data from a database of integrated elderly healthcare at PHC Kedungmundu, focusing on 20 periods from January 2022 to August 2023, and employed a cross-sectional study design. In total, 715 participants were included in the 20 periods. Demographic and vital sign measurement data were merged with those of the respondents. The essential sign measurements were analyzed by age group (45-59, 60-74, and >75) for males and females, and by period using a box plot. Data was analyzed descriptively (proportion, mean, median) using Stata 13. Results: A total of 2,930 participants were included in the 20 periods. Most participants were female (88%) and were between 60 and 74 years old (52%). Healthcare professionals regularly record blood pressure every month, but not all participants provided data on BMI, waist circumference, blood sugar levels, uric acid levels, and cholesterol levels. SBP and DBP were higher in females, especially 60-74 years old (SBP= 141 mmHg, DBP=83 mmHg). BMI (26.04 kg/m2) and waist circumference (87.94 cm) were higher in females than males. Blood sugar (169 mg/dL), uric acid (7.3 mg/dL), and cholesterol (230 mg/dL) data are also higher in females than in males, especially among those aged 45-49 years old. Conclusion: Investigated the health status of the elderly over 20 months, gender and age-related differences in health metrics, and chronic disease risk factors. Tailored health interventions and regular monitoring are crucial for effectively managing and mitigating the risk factors that affect long-term health outcomes and quality of life.